2015
DOI: 10.1016/j.euroneuro.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Stress induced risk-aversion is reverted by D2/D3 agonist in the rat

Abstract: Stress exposure triggers cognitive and behavioral impairments that influence decision-making processes. Decisions under a context of uncertainty require complex reward-prediction processes that are known to be mediated by the mesocorticolimbic dopamine (DA) system in brain areas sensitive to the deleterious effects of chronic stress, in particular the orbitofrontal cortex (OFC). Using a decision-making task, we show that chronic stress biases risk-based decision-making to safer behaviors. This decision-making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 45 publications
(68 reference statements)
1
11
0
Order By: Relevance
“…Whereas in the Honk et al study choice patterns were related to basal cortisol levels, which are a constitutive characteristic of individuals, Kandasamy and colleagues evaluated the impact of cortisol elevation, replicating in a more natural way the impact of chronic stress. Preliminary data from our laboratory demonstrate that a risk‐averse pattern of choice is induced by chronic stress in a rodent risk‐based decision‐making paradigm (Morgado et al, , ), in line with Kandasamy et al's observations.…”
Section: Stress and Risky Decision Makingsupporting
confidence: 84%
“…Whereas in the Honk et al study choice patterns were related to basal cortisol levels, which are a constitutive characteristic of individuals, Kandasamy and colleagues evaluated the impact of cortisol elevation, replicating in a more natural way the impact of chronic stress. Preliminary data from our laboratory demonstrate that a risk‐averse pattern of choice is induced by chronic stress in a rodent risk‐based decision‐making paradigm (Morgado et al, , ), in line with Kandasamy et al's observations.…”
Section: Stress and Risky Decision Makingsupporting
confidence: 84%
“…Levy et al, 2010). These process are likely supported by dopamine action in those regions (Castrellon et al, 2019;Morgado et al, 2015;Soutschek et al, 2020). Although loss aversion and probability weighting seem to be reflected in the striatum and vmPFC like subjective value, they have unique representations in other parts of the brain.…”
Section: Risk and Uncertaintymentioning
confidence: 99%
“…It has been frequently suggested that the anterior insula is relevant for higherlevel processing 42 and risk level, 43 as a consequence of its involvement in learning the negative value of loss-prediction cues. 44,45 Activation of the posterior insula has also been associated with lower risk levels, suggesting that different divisions of the insula play opposing roles during risk processing. In fact, evidence from a meta-analysis is consistent with the proposal that different divisions of the insula are characterized by dissociated connectivity profiles.…”
Section: Healthy Controls Ocdmentioning
confidence: 99%